KESIAGAAN PAKAN PADA TERNAK SAPI SKALA KECIL SEBAGAI STRATEGI ADAPTASI TERHADAP PERUBAHAN IKLIM MELALUI PEMANFAATAN BIODIVERSITAS FLORA LOKAL - Maman Rahmansyah; Arwan Sugiharto; Atit Kanti; I Made Sudiana (Faculty of Animal Science, Universitas Gadjah Mada, 2013)
The presence of local floral resources as forage is essential, especially for the farm survival in anticipaty the impact of the global climate change. The availability of forage in the dry land ecosystems depends on water supply. However, the climate change has caused the change on rainfall pattern including the initiation of the dry season. The problem should be anticipated by the local farmers’ readiness in providing sufficient feed and their ability in performing the excellent management during all seasons. In some areas of East Bali and Nusa Tenggara (West andEast), dry climate crisis 2004 led to feed scarcity. Therefore, this study was conducted in order to identify the potential forage resources in the arid land. The discussion is focused on the results of survey and secondary data collection. Based on the results, there were 22 plants that could be used as forage which were abundant during rainy season, whereas 15 others were able to be forage and silage during the transitional season and along the dry season. The results also showed that the introduction of silage fermentation technique was required as the way to preserve feed for the supply during the dry season. In this study the role of polymer compounds hydrolyzing microbes and the fermentation process by the GRAS (Generally Recognized as Safe) microbes preceeded the role of Lactobacillus plantarum were observed. The results of this study may become a reference in anticipating the global climate change impacts in dry land areas by the application of functional microbial technology in small local farms’ feed management activities.(Key words: Local floral resources, Dry land climate, Fermented feed, Lactobacillus plantarum)